PENERAPAN KOMPOSISI WARNA PADA INTERIOR SEKOLAH PAUD AL-AZHAR 31 DAN 38 DIYOGYAKARTA - Supriyanto Yudi Asmoro (Saraswati)
Schools are places of learning and teaching activities or can also be called a place that is used to study and teach about social interaction. Indonesian government, has launched at least 9 years of learning activities, or often called the FAIR 9 years, starting from the age of 6 years, ranging from elementary school to the Junior High School. This is because the government is hoping that people's lives would beimproved if supported by adequate education. Nowadays people are very concerned about the education of children. Therefore, the parents do not want to wait long to have their children at the age of 6 years. So a lot of children with early childhood isinserted into pre-primary school or often also called early childhood school (Early Childhood Education). This is because the child will more quickly learn and interact at an early age. At an early age, usually the baby will be able to learn easily from the colors seen. Both on interior and furniture color class to place the baby learn. There are many colors that  empangaruhi knowledge of child development, there is also the theory that color can affect how the child develops memory and creation when learning. Education so that children at an early age is very important, and the color is one thing that affects the child's development as well as knowledge. Therefore, researchers are very interested to study the color used on early childhood school. In this case there needs to be discussion about the composition of any color and how the application of color composition in early childhood classrooms Schools AL-AZHAR31 and 38 Yogyakarta.Issues related to the selected the right kind of research to be used is descriptive research kualiatif. Qualitative descriptive study is a way to understand the object of research in the physical and non-physical form, of understanding and frameof the perpetrators themselves about the application of color that covers the interior space in Al-Azhar Kindergarten School 31 and 38 Yogyakarta. Descriptive research is a type of research that is intended to gather information about the status of a variable or theme, symptoms or circumstances that exist according to what it is at the time the study was conducted (Arikunto, 1993:309). Color composition is applied to the interior of the Al-Azhar schools ECD 31 and 38 Yogyakarta is more likely to use a combination or merger of two colors suchas penarapan on the walls and floors that use a combination of primary colors (red, blue, yellow) and secondary colors (green, orange, pink). The merger between the primary and secondary colors, is also used in furniture and props that are in earlychildhood classrooms Al-Azhar 31 and 38 Yogyakarta.Keywords: Color, Interior Early Childhood Education Al-Azhar 31 and 38Yogyakarta